Design & Implementation of a Low Cost Data Logger for Solar Home System - Amit Mazumder Shuvo; Mridha MD. Mashahedur Rahman; Ahnaf Tahmid Nahian; Md. Tahmid Farhan Himel (International Journal of Engineering and Management Research, 2019)
The demand of electric power is increasing gradually with the advancement of modern technology & engineering. Because the demand of electricity in urban areas or in industrial zones is large in amount & also more important than the rural areas, there exists a shortage of electric power supply facilities for rural households or remote location from the cities. In this case, Solar Energy is a promising solution to meet the demand for electricity services of rural areas in developing countries like Bangladesh. The effectiveness & stability of small PV systems for rural development is needed to be monitored for successful installment of Solar Panel. In order to analyze the system & modify it for cost reduction a data capturing unit should be constructed that can store the voltages & currents at three different terminals. A microcontroller operated Smart Data Logger can perform this work with high accuracy & precision maintaining the system cost much less than the conventional system. This paper deals with the design and implementation of a low cost data logger for solar home system. An experimental set up is designed and implemented and the paper illustrates the working principle, data observation and analysis, limitations, and future aspects of a low cost data logger for solar home system.